Sosialisasi dan Implementasi Aplikasi Pemesanan Barang Berbasis Android di UMKM “Mulya PS” - Hidayat, Trifenaus Prabu; Sugioko, Andre; Gunawan, Harjadi; Williana, Catherine (Jurnal Pengabdian Masyarakat Charitas, 2024)
UMKM Mulya PS Shop is a business that sells pet food. The problem faced by the Mulya PS Shop owner is that the shop still uses a sales and service system using manual methods, such as using notes. This problem results in an inaccurate number of orders and income results. As well as problems for consumers, where consumers have to come and order directly at the shop. This makes it difficult for consumers or customers who want to order remotely or outside the area. So based on the problems above, it is necessary to design an information system for making an Android-based goods ordering application and provide socialization of the Android-based goods ordering application to help Mulya PS Shop business owners have complete information and an easy and fast transaction system. By socializing the Android-based application information system, it can help accelerate technology transfer to Mulya PS stores. The application that has been created has fulfilled the purpose of service, namely helping MSME owners and customers, in the goods ordering system and transactions. And the socialization activities have been successfully carried out with good results and are very good at conveying the material and objectives. It is hoped that with this service activity, there will be integration between the Community Service Program and the final assignment courses.